A study on women safety measures to overcome stress - M, Thiagarajan; J, Sridevi (Journal of Management and Science, 2022)
Women is the most precious and powerful source for the overall development of the country through various forms of success in socio-economic, cultural and artistic aspects, sports, health and other personal contentment and wellness. Such a great driving force of power has been suppressed by the hazards of insecurity through the means of violence, inequality and sexual harassments. Statistically, the brutalism against women is increasing to a greater extent. The Constitution of India has been supporting much for the empowerment of women by advocating many laws and legal acts like Domestic Violence Act and Dowry Act which ensures the protection of women from the opposing gender and other torment relations in all means of abuse and demands. Apart from the intrinsic securities, and friends and family shielding, women tend to face various challenging circumstances which results in emotional and psychological pain of stress for them. They should learn to stay strong and have the awareness and safety measures to overcome the stress factors, develop their confidence, and mainly modeling their valor abilities to their children thereby raising a courageous daughter and a responsible son who knows the behavioral and disciplinary patterns towards womanhood. Sexual harassment can jeopardize the victim’s emotional and mental health. It may result in loss of self-esteem and depressive hormonal imbalance. This study aims to find out to what extent the safety measures helps to overcome the stress among women in India.